PENGARUH KUALITAS PELAYANAN, HARGA DAN KETEPATAN WAKTU PENGIRIMAN TERHADAP KEPUASAN KONSUMENPADA PT JALUR NUGRAHA EKAKURIR (JNE) TALUK KUANTAN - Sisi Yuliani; Lie Othman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at PT Nugraha Ekakurir (JNE) Taluk Kuantan on Jalan Imam Munandar, No. 25 Sungai Lintang, Beringin Taluk Village, Kuantan Singingi Regency, Kuantan Tengah District, Riau. partially and simultaneously on consumer satisfaction. The method used in this research is descriptive quantitative, with data sources from primary and secondary data. The analytical method used in this study is simple and multiple linear regression analysis, and with validation tests and reliability tests. In this study the results obtained are: service quality (X1) has a positive and significant effect on consumer satisfaction (Y), price (X2) has a positive and significant effect on customer satisfaction (Y), on time delivery (X3) has a positive and significant effect on customer satisfaction. consumer (Y) at PT Lintas Nugraha Ekakurir (JNE) Taluk Kuantan. Keywords: Service Quality, Price, Timely Delivery, Customer Satisfaction.